2021
DOI: 10.1186/s40364-021-00324-6
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule tyrosine kinase inhibitors modulated blood immune cell counts in patients with oncogene-driven NSCLC

Abstract: Background Lack of biomarkers and in vitro models has contributed to inadequate understanding of the mechanisms underlying the inferior clinical response to immune checkpoint inhibitors (ICIs) in patients with oncogene-driven non-small cell lung cancer (NSCLC). Methods The effect of small molecule tyrosine kinase inhibitors (TKIs) on peripheral blood mononuclear cells (PBMCs) in 34 patients with oncogene-driven NSCLC (cohort A) was compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…Therefore, it is reasonable to hypothesize that a low pre-treatment ALC is associated with a poor response to ICI therapy. Our study confirms this finding in line with previous reports ( 36 , 37 ), showing pre-treatment ALC <600 cells/µL were associated with poor PFS (0.33 vs. 1.35 months; HR 6.9, 95% CI 10.8-25.9, p=0.0053) and poor OS (0.33 vs. 2.34 months; HR 4.66, 95% CI 1.2-17.5, p=0.0236) ( Figure 4 ). Furthermore, patients with ALC <600 cells/µL were less likely to receive a subsequent ICI dose than their counterparts (28.6% vs 36.4%).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, it is reasonable to hypothesize that a low pre-treatment ALC is associated with a poor response to ICI therapy. Our study confirms this finding in line with previous reports ( 36 , 37 ), showing pre-treatment ALC <600 cells/µL were associated with poor PFS (0.33 vs. 1.35 months; HR 6.9, 95% CI 10.8-25.9, p=0.0053) and poor OS (0.33 vs. 2.34 months; HR 4.66, 95% CI 1.2-17.5, p=0.0236) ( Figure 4 ). Furthermore, patients with ALC <600 cells/µL were less likely to receive a subsequent ICI dose than their counterparts (28.6% vs 36.4%).…”
Section: Discussionsupporting
confidence: 94%
“…In recent years, dNLR has been used as a novel biomarker to predict response to immunotherapy in various cancers including NSCLC, melanoma and head and neck cancers ( 39 , 40 ). It has been shown that a high pre-treatment dNLR (indicating a high inflammatory state) is associated with poor OS and PFS in a variety of cancers ( 37 , 39 42 ). For instance, Bongiovanni et al, observed a positive association between OS and a NLR ≤ 5 ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral immune biomarkers in NSCLC present a multifaceted landscape, comprising many components that undergo alterations during natural tumor progression and therapeutic interventions. Our prior investigations have highlighted that anti-cancer agents, including small molecule tyrosine kinase inhibitors and immune checkpoint inhibitors (ICIs), exert modulatory effects on the immune milieu and peripheral blood immune cells of advanced NSCLC patients [137]. For instance, the emergence of post-treatment lymphopenia was discernibly linked with suboptimal clinical outcomes in this patient cohort [138].…”
Section: Immune Cells and Serological Biomarkersmentioning
confidence: 87%